Age and Work Attitudes - Barnes-Farrell, J.; Petery, Gretchen; Cleveland, J.; Matthews, R. (Laurence Erlbaum Associates, 2018)
It has been observed that older workers report more favourable attitudes toward their jobs than those reported by younger workers. However, this is an oversimplified view of the roles of age and aging in the development of positive work attitudes and engagement in work. Therefore, in this chapter we summarize published evidence regarding the nature of relationships between worker age and significant work attitudes, work motives, and work motivation. We also consider individual, developmental, organizational and “outside the workplace” explanations for these relationships. This is followed by a discussion of research questions and methodological consideration that should be addressed for a fuller understanding of how our aging workforce responds to their work situations, and identification of practical recommendations that emerge from what we do know about these issues.